2011
DOI: 10.1007/s12020-011-9486-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes mellitus on vertebral fractures in men with acromegaly

Abstract: Acromegaly is frequently complicated by fragility vertebral fractures and diabetes mellitus. Since type 2 diabetes mellitus is a cause of secondary osteoporosis in the general population, in this cross-sectional study we aimed at investigating the association between diabetes mellitus and vertebral fractures in males with acromegaly. Fifty-seven patients (median age 47 years, range: 24-85) with active (21 cases) and controlled (36 cases) acromegaly and 57 control subjects were evaluated for bone mineral densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 41 publications
4
20
1
1
Order By: Relevance
“…Our study confirmed previous cross-sectional observations in which acromegalic patients developed VFs independent of normal BMD and there were no significant differences in terms of BMD values between fractured and non-fractured patients (14,15,32). For this reason, X-ray assessment is of paramount importance in establishing the real fracture risk in patients affected by acromegaly (33,34) as well as in all patients affected by other forms of secondary osteoporosis (35). In accordance with previous studies (14,15), fracture rate in our population was 43% and the biochemical control of acromegaly appeared effective in reducing the risk of fractures.…”
Section: European Journal Of Endocrinologysupporting
confidence: 90%
“…Our study confirmed previous cross-sectional observations in which acromegalic patients developed VFs independent of normal BMD and there were no significant differences in terms of BMD values between fractured and non-fractured patients (14,15,32). For this reason, X-ray assessment is of paramount importance in establishing the real fracture risk in patients affected by acromegaly (33,34) as well as in all patients affected by other forms of secondary osteoporosis (35). In accordance with previous studies (14,15), fracture rate in our population was 43% and the biochemical control of acromegaly appeared effective in reducing the risk of fractures.…”
Section: European Journal Of Endocrinologysupporting
confidence: 90%
“…A normal to increased BMD has been reported in patients with type 2 diabetes, and it is not entirely explained by overweight [99]. However, an increased risk of fragility fractures occurs in patients with type 2 diabetes, confirming that fractures in secondary osteoporosis cannot be predicted by BMD [99][100][101][102][103][104][105][106]. The risk of fractures in type 2 diabetes is lower than in type 1 diabetes but affects both vertebral and non-vertebral sites [98,107].…”
Section: Diabetes Mellitus and Bonementioning
confidence: 85%
“…Data on BMD in acromegaly are conflicting; however, the effects of non-physiological secretion of GH and IGF-1 appear to affect the bone quality negatively (5,6). Despite normalization of bone turnover following treatment of acromegaly, the risk for vertebral fractures is still increased (5,7).…”
Section: Introductionmentioning
confidence: 99%